Finite element simulation and characterization of one-port heterostructured surface acoustic wave resonator. Issue 1 (26th October 2021) - Turuk, Baruna Kumar; Behera, Basudeba
Abstract: The research work presents the study of a heterostructured surface acoustic wave (SAW) resonator consisting of an interdigital transducer (IDT), lithium niobate (LN), and silicon (Si) substrate. In the proposed structure, Silicon is the base substrate, above it layer of LN is placed then IDT is designed on it. The presented analysis includes the variation of the quality factor and electromechanical coupling coefficient with the change in the width of the piezoelectric layer. The electromechanical coupling coefficient ( K 2 ), quality factor ( Q -factor), velocity, resonance, admittance, and anti-resonance frequency have been studied for the thickness of the different layers of LN film. The higher quality factor of one port SAW devices reduces the energy loss and the K 2 of the devices indicates faster energy conversion. The Q -factor and K 2 are found to be depending on the thickness of LN, resonance, and anti-resonance frequency.